Phenyl glycine incorporated glitazones as promising novel antidiabetic agents through PPARγ agonism: Design, synthesis and preclinical studies - Subhankar Mandal; Devi Sri Chiriki; B.M. Gurupadayya; I.A. Chethan; B.R. Prashantha Kumar (Elsevier, 2022)
Nuclear receptors function as regulators in different anabolic and catabolic pathways. PPARγ, a superfamily of nuclear receptors take part in glucose and lipid metabolism. The functional activation of PPARγ enhances insulin sensitization thereby enhances glucose uptake which results in antidiabetic activity. Present study identifies two novel glitazones of a chemical class 2-amino-2-(4-(2-oxo-2-(substituted phenylamino) ethoxy) phenyl) acetic acid (6a and 6b). They were rationally designed and synthesized specific to the target protein peroxisome proliferator activated receptor gamma (PPARγ). The rational design was executed based on principles of bioisosterism keeping the basic structural requirements of glitazones. The designed glitazones were synthesized, purified, analysed and in silico molecular docking and further molecular dynamics (MD) simulation was performed against PPARγ protein with pioglitazone as reference glitazone. Comparable CDOCKER interaction energy for designed glitazones (6a and 6b) [(−) 46.1385 and (−) 45.8841 ​kcal/mol] were observed against standard pioglitazone [(−) 49.8236 ​kcal/mol). The IC50 values of 5.61 and 6.82 ​μM were evaluated from protein binding assay via time resolved fluorescence test (TR-FRET). The promising results motivated us to evaluate 6a for in vivo pharmacokinetic profile and anti-diabetic assay. The 6a showed significant antidiabetic activity compared with the pioglitazone in the streptozotocin (STZ) induced rat model. Interestingly, for 6a, improved T1/2 (half-life) of 3.0855 ​± ​0.29 ​h and Kel (elimination rate constant) of 0.2246 ​± ​0.19 was observed as compared to the pioglitazone, depicting better pharmacokinetic profile for novel glitazone. Altogether, the preclinical study of 6a was promising via activation of PPARγ receptors.